Halal Clauses in the Agreement on Reciprocal Trade (ART) between Indonesia and the United States: Sharia Perspectives and Indonesia's Halal Policy - Qiwamudin; Nur Fatwa; Nurwahidin (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the comparison and conformity between Indonesian halal regulations and halal clauses in the Agreement on Reciprocal Trade (ART) articles 2.9 and 2.22 between the Republic of Indonesia and the United States. The analysis in this study uses a normative juridical method with a statutory approach, a comparative approach and a conceptual approach, this study dissects nine points in the halal clause of the ART. The results of the study show that there is a significant disparity in norms, namely three paragraphs declared appropriate, two partially contradictory paragraphs, and four absolute contradictory paragraphs because it is not in accordance with Indonesian halal regulations, especially related to the labeling of non-halal products and the elimination of halal supervisors. Judging from Hans Kelsen's sovereignty theory, Indonesia has the legal capacity to maintain its national standards to protect citizens, which is emphasized through the Decree of the Head of BPJPH No. 221 of 2025 regarding foreign halal certification. In sharia principles, the rejection of contradictory clauses is the implementation of the rules of Dar'ul Mafāṣid Muqaddam 'Alā Jalbil Maṣāliḥ in order to ensure halal certainty and the protection of Indonesian Muslims.